Chimney and Periscope Grafts to Facilitate Endovascular Treatment of Aortic Transection in a Patient With Aberrant Right Subclavian Artery. (February 2014) - Vicente, Sandra; Glenck, Michael; Mayer, Dieter; Veith, Frank J.; Lachat, Mario; Pecoraro, Felice
Purpose: To report the use of parallel grafts to extend the proximal landing zone for stent-graft repair of aortic transection involving an aberrant right subclavian artery (ARSA). Case Report: A 28-year-old patient was referred for treatment of traumatic aortic transection with contained rupture at the level of an ARSA. Immediate thoracic endovascular aortic repair (TEVAR) was planned because of hemodynamic instability. To achieve rapid sealing and maintain perfusion to both subclavian arteries, a chimney stent to the left subclavian artery (LSA) and a periscope stent-graft to the ARSA were deployed successfully. After surgical repair of all fractures, the patient was discharged 1 month after the initial injury in good condition. Imaging follow-up at 10 months showed a stable repair, patent parallel grafts, and no complications. Conclusion: TEVAR with chimney and periscope grafts proved to be a safe and quick treatment for a patient requiring ARSA repair in acute aortic transection. This technique maintained blood flow to the ARSA and LSA in a totally endovascular approach, which could be very valuable in transection cases where bypass surgery to supra-aortic branches is compromised or deemed challenging due to thoracic wall and/or neck trauma. Parallel grafting can be a valuable tool to address any acute aortic pathology as it can be performed with off-the-shelf devices.